O balneário castrejo do Castro das Eiras - Queiroga, Francisco Reimão; Dias, António Pereira (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
The Iron Age sauna uncovered in 1990 at the Eiras hillfort added new evidence for the understanding of these interesting and somewhat rare structures. The bath structure bears an unusual large size and profuse decoration of its granite-composing elements. It is a prestige utility within a large urban site built under Roman guidance, although its typology is indigenous. The craftsmanship and decorative typologies involved suggest the existence of specialized itinerant masons.